2017
DOI: 10.1007/s11368-017-1729-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling sediment trapping in two freshwater tidal wetlands in the Biesbosch area, The Netherlands

Abstract: Purpose A thorough understanding of mechanisms controlling sedimentation and erosion is vital for a proper assessment of the effectiveness of delta restoration. Only few field-based studies have been undertaken in freshwater tidal wetlands. Furthermore, studies that measured sediment deposition in newly created wetlands are also sparse. This paper aims to identify the factors controlling the sediment trapping of two newly created freshwater tidal wetlands. Materials and methods Two recently re-opened polder ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 55 publications
2
28
2
Order By: Relevance
“…The most landward wetland we sampled at rkm 228 is presumably directly exposed to effects of the dam, but had a positive accretion rate consistent with its protected position on an inlet enclosed by an island. The potential role of winds in sediment transport and trapping efficiencies (Prokocki et al., 2020; van der Deijl et al., 2017) was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…The most landward wetland we sampled at rkm 228 is presumably directly exposed to effects of the dam, but had a positive accretion rate consistent with its protected position on an inlet enclosed by an island. The potential role of winds in sediment transport and trapping efficiencies (Prokocki et al., 2020; van der Deijl et al., 2017) was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Van der Deijl et al (2017) identified the factors controlling the sediment trapping of two newly created freshwater tidal wetlands under varying conditions of river discharge, tide, and wind in the Netherlands. A positive sediment budget and trapping efficiency was found where there was a continuous supply of river water and sediment, while sediment was lost where the wetland lies further from the river and had a lower sediment supply.…”
Section: Sources and Fate Of Sediments And Contaminantsmentioning
confidence: 99%
“…
Estuaries are bodies of water with one or more open connections to the sea (Leuven et al, 2016) which develop at the land-sea interface due to delivery of sediment from both rivers and the coast (Nicholls et al, 2020). Estuaries that have developed naturally tend to have a converging planform shape, often with mutually evasive ebb and flood channels which create a multi-channel system (Jeuken & Wang, 2010;van Dijk et al, 2021;Weisscher et al, 2022). They have several intertidal shoals and bars, particularly at their widest points (Leuven et al, 2016), and extensive floodplains (van Veen et al, 2005).
…”
mentioning
confidence: 99%
“…Dredging activities can be broadly split into two categories: (a) capital dredging events, which deepen channels permanently, and (b) maintenance dredging, which is the periodic process of keeping channels at a specific depth. Typically, systems undergo capital dredging every 10-20 years, while maintenance dredging typically occurs year-round, particularly in systems that are home to large ports (Cox, Dunn, et al, 2021;Cox, Huismans, et al, 2021;van Dijk et al, 2021). The dredged material can be either completely removed from the system (sold to market or dumped offshore) or reused and relocated within the system.…”
mentioning
confidence: 99%